Dinámica no markoviana en complejos de colision electron-molecula (1993)
It is studied the time dependent description of electron-molecule collision complexes is studied. It is shown that the equation of motion for the. wave packet is non-Markovian, that is, the time development depends on the previous history of the system. The integro-differential equation of motion is explicitly solved.